Preseason variations in aerobic fitness and performance in elite-standard soccer players: A team study - Castagna, C.; Impellizzeri, F. M.; Chaouachi, A.; Manzi, V. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to examine the effects of individual training loads considered as permanent in selected heart-rate (HR) zones on aerobic fitness and performance in elite professional soccer players. Eighteen professional soccer players were observed during the prechampionship training period (8 weeks). Speeds and HR at 2 and 4 mmol/L blood-lactate concentrations (S2, S4, respectively), VO2max, and Yo-Yo intermittent recovery test level 1 performance (Yo-Yo IR1) were assessed pretraining and posttraining. Training intensities were categorized using 3 HR zones: low intensity (<HR 2 mmol/L), moderate intensity (between HR 2 and 4 mmol/L), and high intensity (>HR 4 mmol/L). Training-session HRs (n = 900) showed a polarized distribution with 73.6 ± 3.7 (2,945 ± 148 minutes), 19.1 ± 3.5 (763 ± 141 minutes), and 7.3 ± 2.9% (292 ± 116 minutes) of the total training time spent at low, moderate, and high intensities, respectively (p < 0.001). The S2 and S4 significantly improved posttraining (+10 and 7%, respectively, p < 0.001). The VO2max and Yo-Yo IR1 values were 6 and 19.5% higher posttraining, respectively (p < 0.01). Training performed at high intensity was significantly related to relative improvement in S2 (r = 0.78, p = 0.002), S4 (r = 0.60, p = 0.03), VO2max (r = 0.65, p = 0.02), and Yo-Yo IR1 (r = 0.66, p = 0.01). The results of this study provided further evidence for HR longitudinal validity and effectiveness of the high-intensity training (i.e., >90% HRmax) in men`s professional soccer. In this regard, the time spent at high intensity should be in the range of 7-8% of the total training time during preseason.